Comparison principles for infinity-Laplace equations in Finsler metrics. (January 2020) - Mebrate, Benyam; Mohammed, Ahmed
Abstract: In this paper we study comparison principles for normalized Finsler infinity-Laplace operators with nonhomogeneous terms that depend on solutions and their gradients. This is achieved by using a combination of sup-convolution methods to approximate viscosity solutions by semiconvex functions and finite difference approximation schemes. Characterizations of viscosity subsolutions and supersolutions of equations with constant nonhomogeneous terms through comparison with quadratic Finsler cone are also discussed.